Mind‐Body CAM Interventions: Current Status and Considerations for Integration Into Clinical Health Psychology. Issue 1 (30th August 2012) - Park, Crystal
<x xml:space="preserve">Abstract</x> Objective Complementary and alternative medicine (CAM) is increasingly used for treating myriad health conditions and for maintaining general health. The present article provides an overview of current CAM use with a specific focus on mind‐body CAM and its efficacy in treating health conditions. Method Characteristics of CAM users are presented, and then evidence regarding the efficacy of mind‐body treatments (biofeedback, meditation, guided imagery, progressive muscle relaxation, deep breathing, hypnosis, yoga, tai chi, and qi gong) is reviewed. Results Demographics associated with CAM use are fairly well‐established, but less is known about their psychological characteristics. Although the efficacy of mind‐body CAM modalities for health conditions is receiving a great deal of research attention, studies have thus far produced a weak base of evidence. Methodological limitations of current research are reviewed. Suggestions are made for future research that will provide more conclusive knowledge regarding efficacy and, ultimately, effectiveness of mind‐body CAM. Considerations for clinical applications, including training and competence, ethics, treatment tailoring, prevention efforts, and diversity, conclude the article. Conclusions Integration of CAM modalities into clinical health psychology can be useful for researchers taking a broader perspective on stress and coping processes, illness behaviors, and culture; for practitioners seeking to incorporate CAM perspectives into their work; and for policy makers in directing healthcare resources wisely.